Religious Pluralism Revisited: Discursive Patterns of the Ulama Fatwa in Indonesia and Malaysia - Hasyim, Syafiq (Center for Study of Islam and Society (PPIM) Syarif Hidayatullah State Islamic University, 2019)
As a long-established fundamental value of both Indonesia and Malaysia, religious pluralism has become a highly contested issue. A common tendency among the dominant Muslim groups in Indonesia and Malaysia, promoted by their fatwa bodies, has been to revisit religious pluralism. This article poses questions: how pluralism is defined, discussed and contested in both countries; why mainstream Islamic groups reconstruct the meaning of the term; which arguments are used by these groups; and what impact this has on legal discourse and legal practice in both countries. With these questions, this article focuses on fatwas issued by the Indonesian Council of Ulama and the National Fatwa Council of Malaysia. The article discusses the incorporation of fatwas into state policy in both countries, social disputes and contestation over fatwas. The theoretical frameworks used are taken from interdisciplinary discourses on transnationalism, pluralism, Islamic legal theory, legal pluralism and the public sphere.